Physical Education Learning Application Based on Android Platform - Dita Helviani; Herman Herman; Eko Prabowo; Slamet Sukriadi (Musamus Journal of Physical Education and Sport (MJPES), 2024)
Objective. This study is focused on creating an Android-based physical education learning system for 7th-grade students at SMPN 3 Cibinong. The goal is to enable students to easily access physical education resources anytime and anywhere. The Android application being developed will feature an appealing splash screen, a home screen with chapters for learning, a section for physical education study materials, an evaluation screen with assessment questions, a reference section with a bibliography, and comprehensive learning materials including videos, images, and written content aligned with the learning objectives. Materials and methods. This research was conducted using the research and development method and implemented the ADDIE model, which includes analysis, design, development, implementation, and evaluation to achieve suitable development of Android-based physical education learning. Results. Based on the findings of the study, the application appears to facilitate easier and more effective learning, making it simpler for students to comprehend all aspects of physical education. The expert evaluation involved three learning experts, two physical education lecturers, and a physical education teacher. Conclusion. The Android-based physical education learning application was found to have an overall satisfaction rate of 95%. It is considered suitable for use as a learning resource because of its ease of access and clear, comprehensive content including videos, images, and text. It also makes the learning process easier and can be used repeatedly.